Factors Affecting Auditory Estimates of Virtual Room Size: Effects of Stimulus, Level, and Reverberation. (July 2021) - Kolarik, Andrew J.; Moore, Brian C. J.; Cirstea, Silvia; Aggius-Vella, Elena; Gori, Monica; Campus, Claudio; Pardhan, Shahina
When vision is unavailable, auditory level and reverberation cues provide important spatial information regarding the environment, such as the size of a room. We investigated how room-size estimates were affected by stimulus type, level, and reverberation. In Experiment 1, 15 blindfolded participants estimated room size after performing a distance bisection task in virtual rooms that were either anechoic (with level cues only) or reverberant (with level and reverberation cues) with a relatively short reverberation time of T 60 = 400 milliseconds. Speech, noise, or clicks were presented at distances between 1.9 and 7.1 m. The reverberant room was judged to be significantly larger than the anechoic room ( p < .05) for all stimuli. In Experiment 2, only the reverberant room was used and the overall level of all sounds was equalized, so only reverberation cues were available. Ten blindfolded participants took part. Room-size estimates were significantly larger for speech than for clicks or noise. The results show that when level and reverberation cues are present, reverberation increases judged room size. Even relatively weak reverberation cues provide room-size information, which could potentially be used by blind or visually impaired individuals encountering novel rooms.